Peran Pelayan Gereja untuk Meningkatkan Kehadiran Kaum Bapa dalam Beribadah Ke Gereja - Anton Sitorus; Frenty Sariyati; Benny Christian Hutabarat; Tetty Sunarti Nainggolan; Berton Bostang Silaban (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Church congregations generally include ,men, women, youth, teenagers and children. It should be that when worship is held, all elements of the church gather and worship together. However, in reality there is an imbalance in the number of congregations present at church from the number of congregation members who attend each week. At GMI Pulau Sibandang, this occurs in the number of Men who attend worship every week. This study was written to analyze the role of GMI Pulau Sibandang servants in increasing the presence of fathers in worshiping at church. The research method used literature review, informal interviews and also observations at GMI Pulau Sibandang. The results showed that there were several factors causing fathers to not attend church services. This encouraged GMI Pulau Sibandang servants to pay attention to these factors and implement strategies to overcome this.